(x-5)(y-3)=

Simple and best practice solution for (x-5)(y-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-5)(y-3)= equation:


Simplifying
(x + -5)(y + -3) = 0

Reorder the terms:
(-5 + x)(y + -3) = 0

Reorder the terms:
(-5 + x)(-3 + y) = 0

Multiply (-5 + x) * (-3 + y)
(-5(-3 + y) + x(-3 + y)) = 0
((-3 * -5 + y * -5) + x(-3 + y)) = 0
((15 + -5y) + x(-3 + y)) = 0
(15 + -5y + (-3 * x + y * x)) = 0
(15 + -5y + (-3x + xy)) = 0

Reorder the terms:
(15 + -3x + xy + -5y) = 0
(15 + -3x + xy + -5y) = 0

Solving
15 + -3x + xy + -5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -3x + xy + -15 + -5y = 0 + -15

Reorder the terms:
15 + -15 + -3x + xy + -5y = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -3x + xy + -5y = 0 + -15
-3x + xy + -5y = 0 + -15

Combine like terms: 0 + -15 = -15
-3x + xy + -5y = -15

Add '5y' to each side of the equation.
-3x + xy + -5y + 5y = -15 + 5y

Combine like terms: -5y + 5y = 0
-3x + xy + 0 = -15 + 5y
-3x + xy = -15 + 5y

Reorder the terms:
15 + -3x + xy + -5y = -15 + 5y + 15 + -5y

Reorder the terms:
15 + -3x + xy + -5y = -15 + 15 + 5y + -5y

Combine like terms: -15 + 15 = 0
15 + -3x + xy + -5y = 0 + 5y + -5y
15 + -3x + xy + -5y = 5y + -5y

Combine like terms: 5y + -5y = 0
15 + -3x + xy + -5y = 0

The solution to this equation could not be determined.

See similar equations:

| 4/5*x-7/10*x=4 | | 5k^2+17k-22=0 | | (x-3)(y+6)= | | 4/15/5/7 | | -1/2x-2=0 | | P=5Q+7 | | 4x^2+19x-23=0 | | (x+2)(y+4)= | | X-94=-5x+2 | | X^4-10x-50=0 | | Y-C=S | | .5x=197125 | | .05x=197125 | | 3/11 | | -2(3n+2)=4 | | y^2+6y-28=0 | | 8(y-5)/3=-2y | | 3.14*100*h=4710 | | X(7.8-1.2)=54.2 | | (2x+13)(x-3)=0 | | Y=38+7.7x | | log(x+13)-log(2)=log(3x+3) | | 7x=28000000 | | 0.60x+0.85*30=0.30*97 | | 2(6x-13)= | | log(x+13)-log(2)=log(2x+3) | | 43-2[6+(3+2)]= | | 0.03x+0.15(70)=0.15(82) | | 2x+x+6=8 | | Sin(2x)cos(x)=sin(x)cos(2x) | | -4/5(-19/16) | | 12+3[5+(4-2)]= |

Equations solver categories